PENGEMBANGAN UNIT MODUL PEMBELAJARAN EKOLOGI TUMBUHAN BERDASARKAN KOMPOSISI DAN STRUKTUR VEGETASI STRATA SAPLING DI KAWASAN HUTAN MANGROVE KABUPATEN SIAK - Nursal, ' '; Yuslim Fauziah '; Erizal ' ' (Biogenesis, 2014)
The research of compotition and structure of sapling vegetation at mangrove forest Siakdistrict Riau province had been carriedout on February- Apryl 2014 by survey methodswith plots (10x5) m 2 and transects.The transect was taken place 100 m from coastline. Eachindividual of saplings that account in the plot was measured diameter of breast high. Theparameter were species vegetation, density, frequency, dominancy, importance values,diversity index and similarity index. The results of this research account 11 saplings ofmangrove vegetation at mangrove forest Siak district, they are Avicennia alba, Bruguieragymnorhiza, Excoecaria agallocha, Heritiera littoralis, Hibiscus tiliaceus, Lumnitzeralittorea, Rhizophora apiculata, Rhizophora mucronata, Scyphiphora hydrophillacea,Sonneratia alba and Xylocarpus granatum. Based on index values obtained importantspecies that dominate at each station is Rhizophora apiculata (St.I and III), Xylocarpusgranatum (St.II), and Sonneratia alba (St.IV). Diversity index of sapling vegetation atmangrove forest Siak districtwas moderate. Similarity index analysis of sapling vegetationat mangrove forest Siak district showed that there similarities between the saplingvegetation at I station with III station (IS=54.5%), II station with III station (61.5%), IIstation with IV station (IS=50%) and III station with IV station (76.9%). The results ofthis research was developed into units of learning modules on plant ecology course andthe title is Mangrove Community. Validation results indicate that this unit module is validand can be used by students to learning plant ecology.Keywords: Vegetation, Sapling, Mangrove